Gender, religion and diversity : cross-cultural perspectives - King, Ursula; Beattie, Tina, 1955- (Continuum, 2005)
Gender, Religion and Diversity provides an introduction to some of the most challenging perspectives in the contemporary study of gender and religion. In recent years, women's and gender studies have transformed the international study of religion through the use of interdisciplinary and cross-cultural methodologies, which have opened up new and highly controversial issues, challenging previous paradigms and creating fresh fields of study. As this book shows, gender studies in religion raises new and difficult questions about the gendered nature of religious phenomena, the relationship between.